PENGARUH KOMPENSASI, MOTIVASI DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN BANK SYARIAH â€œXâ€ DI SURABAYA - Hanif Fadhlillah; Himmatul Kholidah; Hanifiyah Yuliatul Hijriah (Jurnal Ilmiah Ekonomi Islam, 2023)
The purpose of this research was to determine the effect of compensation, motivation and organizational culture on employee performance. The subject of this research is Bank Syariah â€œXâ€ di Surabaya. Respondents or population in this research are all permanent employees in the office of Bank Syariah â€œXâ€ in Surabaya totaling 194 employees. Respondents were more than 100 people, the researchers used purposive sampling in the sampling and obtained 65 employees as respondents and data collection tools used questionnaire analysis method used is multiple linear regression with SPSS. The results of this research indicate that compensation significantly influence employee performance, motivation significant effect on employee performance and organizational culture have a significant effect on employee performance Keywords: Compensation, Employee Performance, Motivation, Organizational Culture,